WNT2b Activates Epithelial-mesenchymal Transition Through FZD4: Relevance in Penetrating Crohn´s Disease - Ortiz-Masià, Dolores; Salvador, Pedro; Macias-Ceja, Dulce C; Gisbert-Ferrándiz, Laura; Esplugues, Juan V; Manyé, Josep; Alós, Rafael; Navarro-Vicente, Francisco; Mamie, Céline; Scharl, Michael; Cosin-Roger, Jesus; Calatayud, Sara; et al. (Journal of Crohn's and colitis, 2020)
Abstract Background and Aims Epithelial-mesenchymal transition [EMT] has been related to fibrosis and fistula formation, common complications associated with Crohn´s disease [CD]. The WNT signalling pathway mediates EMT, and specific WNT/FZD interactions have been related to the activation of this process in several diseases. We aim to analyse the relevance of EMT and WNT ligands and receptors in the penetrating behaviour of CD. Methods Intestinal surgical resections were obtained from control and CD patients with a stenotic or penetrating behaviour. Fibrosis was determined by the histological analysis of collagen deposition and EMT by confocal microscopy. The expression of WNT ligands, inhibitors, and FZD receptors was analysed by RT-PCR, WB, IH, and IF studies. The effects of WNT2b and the role of FZD4 in EMT were analysed in HT29 epithelial cells. Results Fibrosis and expression of EMT markers were detected in samples from CD patients irrespective of the clinical behaviour. However, an increased colocalisation of E-CADHERIN and VIMENTIN, an increased number of cells expressing WNT2b, and a higher expression of FZD4 and WNT2b/FZD4 interaction, were detected in intestinal tissue from the penetrating compared with the stenotic CD behaviour. WNT2b induced EMT in HT29 cells through FZD4 activation. Conclusions An increased EMT, associated with increased WNT2b/FZD4 interaction, was detected in intestinal tissue from CD patients with a penetrating behaviour. WNT2b, through FZD4 activation, induces EMT in vitro which points to a novel pharmacological target to prevent intestinal penetrating complications of CD.